2013
DOI: 10.1021/es4048347
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Dose Cadmium Exposure on DNA Methylation in the Endangered European Eel

Abstract: There is increasing evidence that epigenetics can play a key role in the etiology of diseases engendered by chronic pollutant exposure. Although epigenetics has received significant attention in the field of biomedicine during the last years, epigenetics research is surprisingly very limited in ecotoxicology. The aim of the present study was to investigate the possible effects of low-dose cadmium exposure on the DNA methylation profile in a critically endangered fish species, the European eel. Eels were expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(40 citation statements)
references
References 37 publications
2
38
0
Order By: Relevance
“…A similar effect was also described in human prostate cell lines during Cd-induced malignant transformation [19]. Eels exposed to 0.4 and 4 μg/L Cd were associated with a significant increase in the global CpG methylation status [50] as well as human embryo lung fibroblast cells after long-term, low-dose Cd exposure [51]. DNA methylation levels and the gene expression of DNMT1 and DNMT3a in hens’ liver and kidney were significantly elevated by Cd treatment [52].…”
Section: Discussionmentioning
confidence: 62%
“…A similar effect was also described in human prostate cell lines during Cd-induced malignant transformation [19]. Eels exposed to 0.4 and 4 μg/L Cd were associated with a significant increase in the global CpG methylation status [50] as well as human embryo lung fibroblast cells after long-term, low-dose Cd exposure [51]. DNA methylation levels and the gene expression of DNMT1 and DNMT3a in hens’ liver and kidney were significantly elevated by Cd treatment [52].…”
Section: Discussionmentioning
confidence: 62%
“…Other factors, such as epigenetic effects (induction of phenotypic variation without DNA sequence alteration) (Pierron et al, 2014;Richards, 2006), may also explain the observed differences in gene expression between the two fish groups (Pierron et al, 2014). Indeed, although the yellow perch populations used in this study were similar in body weight and length and originated from the same region with similar natural macro-environments, epigenetic mechanisms could exert a crucial influence on phenotypic plasticity and on the interactions between the fish and their environment, thereby modifying gene expression and contributing to environmentally-induced phenotypic changes (Angers et al, 2010).…”
Section: Time Scale Of Changes In Metabolic Responses and Metal Genommentioning
confidence: 99%
“…In addition, Morán et al [17] showed that salt diets used during the seawater phase triggered genome-wide methylation changes when administered in freshwater reared trout indicating that DNA methylation could play a vital role in enabling anadromous ish acclimatize to seawater after transfer from freshwater. DNA methylation and histone modiication have also been associated with adaptation changes induced by adverse environmental conditions as shown in Nile tilapia exposed to industrial pollutions [231], eels to cadmium exposure [232], sea urchin (G. crenularis) exposure to perluoroctane sulfonate (PFOS) [216] and the three-spine stickleback (G. aculeatus) hexabromocyclododecane (HBCD) exposed to 17-β oestradiol (E 2 ) and 5-aza 2′ deoxycytidine (5AdC) pollutants [233]. In summary, these studies demonstrate that DNA methylation and histone modiication contribute to nutritional, environmental and photoperiod adaptation in diferent aquatic organisms and that these factors could have an inluence on improving production in aquaculture.…”
Section: Adaption Epigenetic Traitsmentioning
confidence: 99%